2004
DOI: 10.1016/j.ydbio.2003.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Timed interactions between the Hox expressing non-organiser mesoderm and the Spemann organiser generate positional information during vertebrate gastrulation

Abstract: We report a novel developmental mechanism. Anterior-posterior positional information for the vertebrate trunk is generated by sequential interactions between a timer in the early non-organiser mesoderm and the organiser. The timer is characterised by temporally colinear activation of a series of Hox genes in the early ventral and lateral mesoderm (i.e., the non-organiser mesoderm) of the Xenopus gastrula. This early Hox gene expression is transient, unless it is stabilised by signals from the Spemann organiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
195
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(209 citation statements)
references
References 79 publications
14
195
0
Order By: Relevance
“…The most 3 0 anterior Hox genes are expressed first and progressively more 5 0 posterior Hox genes are expressed progressively later. This temporally collinear sequence is used to generate the primary spatial A-P Hox pattern by time space translation and to integrate all of the successive derived patterns (Wacker et al, 2004;Durston et al, 2010). This is thus a different situation than in Drosophila, where the primary pattern guiding Hox spatial collinearity is generated externally, by the gap and segmentation genes.…”
Section: Posterior Prevalence Is Unique To Vertebrates: Is Time Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The most 3 0 anterior Hox genes are expressed first and progressively more 5 0 posterior Hox genes are expressed progressively later. This temporally collinear sequence is used to generate the primary spatial A-P Hox pattern by time space translation and to integrate all of the successive derived patterns (Wacker et al, 2004;Durston et al, 2010). This is thus a different situation than in Drosophila, where the primary pattern guiding Hox spatial collinearity is generated externally, by the gap and segmentation genes.…”
Section: Posterior Prevalence Is Unique To Vertebrates: Is Time Of Thmentioning
confidence: 99%
“…The involuting gastrula mesoderm acquires patterning information first and this mesoderm then copies information to an adjacent tissue layer, the overlying neurectoderm, which develops a clear A-P pattern by the end of gastrulation. This copying process is called vertical signalling (Mangold, 1933;Wacker at al., 2004;Durston et al, 2010). The mesoderm thus copies A-P information onto the neurectoderm.…”
Section: Posterior Prevalence Is Unique To Vertebrates: Is Time Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the non-organiser mesoderm (NOM) of the Xenopus laevis gastrula, where Hox genes are first expressed in the embryo and are expressed with temporal colinearity (Fig.4a). This mesoderm manifests a sharply timed temporally collinear sequence of Hox gene expression that is translated in time and space by interactions with the Spemann organiser (SO) to to generate a spatially collinear pattern of Hox gene expression along the main body axis of the organism (Wacker et al, 2004a;Durston et al, 2010Durston et al, , 2011 The mechanism for this is shown in Figure 4b. .In short, the temporal sequence of Hox gene expression in the mesoderm is sequentially frozen, from anterior to posterior and is transferred to the developing neural plate, which overlies the internalising mesoderm, in the gastrula.…”
Section: Hox Genes In Gastrulationmentioning
confidence: 99%
“…4A). The temporal collinearity of the different Hox complexes is therefore synchronised (Wacker et al, 2004a;Durston et al, 2010Durston et al, , 2011 . The different Hox paralogues (ie the different copies of each different Hox gene type, produced by the vertebrate genome duplications) in the different complexes are on different chromosomes, ruling out that Hox colinearity simply reflects cis-localised progressive opening of Hox complex chromatin for transcription.…”
Section: Hox Genes In Gastrulationmentioning
confidence: 99%